TEKS LONTAR TUTUR RARE ANGON (Kajian Filosofis Hindu Tentang Eksistensi Manusia) - I Made Suweta (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2020)
Talks on the philosophical level can be done in various disciplines, such as ethics, aesthetics, language, mathematics, history, and so on. Similarly, philosophical analysis related to human existence can also be done. In relation to human philosophy, there are also in the Lontar in Bali. Not only one or two Lontar alone describes the philosophy of man, but there are many lontar. One of the lontar that has been shaped text is the text Tutur Rare Angon. The important issue that will be addressed in this article is how the human existence in the text of the Lontar TuturÂ  Rare Angon seen from a Hindu philosophical perspective.Philosophically, human existence in the study of text Lontar Tutur Rare Angon consists of three things, namely individuals, social and religious. In the text of Tutur Rare Angon individual is shown at the ceremony of the loss of a central cord in infants up to sixteen years of age according to the stage, hope to keep the baby and its existence as human beings. Through the ceremony it can improve the spiritual existence of individuals taught through the concept of Hindu religion. In the text of Tutur Rare Angon, concerning the reiligiusitas of the Hindu people who demonstrated through the mention of the term deity. In every aspect and process of human life there are divine elements. Human Moral in the text of Tutur Rare Angon in the study of the text Tutur Rare Angon is the goodness found in the text of Tutur Rare Angon relationship with fellow man and moral with nature. Goodness in the text Tutur Rare Angon mentions that man must have good moral, should not lie. A man who lies will have a great sin. Because lying is a wrong action or word is conveyed by someone or to others in order to be trusted but not in accordance with the facts. Relationship with our fellow man, one must be equal to a friend or an enemy, not favoring one, not hating one and always forward-thinking. The Moral with nature in the text Tutur Rare Angon mentions that humans should always keep Mother Earth and the universe by not buried the dead body on the ground over a given time limit.